O estresse e sua relação com o desempenho acadêmico: um estudo com graduandos de Ciências Contábeis e Administração - Silva, Taís Duarte (2018)
The trajectory of a university student begins by entering higher education, which is marked by the choice of profession and it involves numerous challenges that impose the need to adapt to intense changes. This process of transformation comprises not only academic aspects, as it covers their life in many aspects. Thus, studies from diverse areas have pointed out the incidence of psychological adversities in the period of study, such as stress. This phenomenon has been investigated mainly in relation to its causes and possible implications in the academic environment. In this scenario, the purpose of this study was to investigate the relationship between stress and academic performance in undergraduate students of Accounting Sciences and Administration at a federal public higher education institution. In order to fulfill this objective, it investigated 684 students: 59.94% of Accounting Sciences and 40.05% of Administration. Through a descriptive analysis, it verified that 51.17% of the respondents are highly stressed. It used multiple linear regression analysis to investigate possible factors that could relate to the level of stress. Among the results, there is a significant relationship between the variables gender and income, showing that female students with lower family income had higher levels of stress; and the lack of motivation, which is among the most frequent stressors and it presented a significant and directly proportional relation with stress. To evaluate the relationship between stress and students’ academic performance, it used the Spearman correlation test, which showed a negative, but not significant relationship. Moreover, the variables income and hours of study present a significant relationship with student performance. The findings show that the stress is notorious, but it was not related to the students’ academic performance. Therefore, it is necessary to focus on the main elements related to stress, because in excess it may have diverse consequences in students' lives.